Keterkaitan Sektor Industri Pengolahan Terhadap Perekonomian Sulawesi Selatan (Analisis Input-Output) - Mahdy. K, Muh. Raihan Eka; Hastuti, Diah Retno Dwi; Bado, Basri; Samsir, Andi; Astuty, Sri (Universitas Negeri Padang, 2025)
wealth of natural resources and the presence of various industries utilizing these resources, South Sulawesi exhibits diverse potential within the processing industry. This potential can be harnessed to enhance the economy of South Sulawesi Province, which is still classified as a developing region. This study aims to analyze the interconnections between the processing industry sector and other sectors, as well as to identify key sectors within the processing industry and the output multiplier effects generated using Input-Output analysis methods. The analysis results indicate that most processing industry sectors are capable of stimulating production growth in other sectors through the utilization of the generated output. Conversely, only the food and beverage industry and the non-metallic mineral products industry are sensitive to final demand, suggesting that these sectors are key. Based on the output multiplier figures obtained, the food and beverage sector demonstrates the highest value.